Factors to Measure the Performance of Private Business Schools in South Africa - Asvat, R; Bisschoff, CA; Botha, CJ (Journal of Economics and Behavioral Studies, 2018)
This article identifies the latent variables embedded within the model to measure the performance of private business schools. In the quantitative research design, 247 questionnaires, using a five-point Likert scale, were analysed after completion by private business school supervisors and managers. The data has high reliability with a Cronbach alpha coefficient of 0.974 and excellent sample adequacy with a KMO value of 0.926. The analysis identified ten latent variables (or factors), identified using exploratory factor analysis explaining a cumulative variance of 70.56%. These are Regulatory compliance, Strategic communication, Educational technology stack, Strategic finance, Organisational development, Customer orientation, Sales, Pricing, Socio-political influence and Market focus. The study also succeeded to simplify measuring performance by eliminating 26 questions with low factor loadings (<0.40) or those that are cross-loading highly onto more than one factor from the questionnaire while retaining a satisfactory level of reliability. The results are valuable to private business school managers and to the employees wanting to measure and improve the business performance of a private business school. Researchers and academia could also benefit from the contribution of the study to either build on business performance of private business schools or, alternatively, in adopting the methodology employed in this study for another application setting.